2009
DOI: 10.1111/j.1742-1241.2008.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary Sjogren’s syndrome in Turkey: a population-based epidemiological study

Abstract: The pSS prevalence rates found in the Turkish population in this study were lower than the estimated prevalence rate in a general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 22 publications
2
24
0
2
Order By: Relevance
“…A Turkish study reported by Birlik et al estimated the prevalence of pSS at 0.35 (95% CI 0.10–0.45) using the European criteria and 0.21 (95% CI 0.03–0.29) using the revised AECG criteria 12. The third study, a cross-sectional population based survey in Turkey by Kabasakal et al, estimated the prevalence of pSS in women aged 18–75 years at 1.56 (95% CI 0.92–2.66) using the European Criteria and 0.72 (95% CI 0.33–1.57) using the revised criteria 13…”
Section: Classification Criteriamentioning
confidence: 99%
“…A Turkish study reported by Birlik et al estimated the prevalence of pSS at 0.35 (95% CI 0.10–0.45) using the European criteria and 0.21 (95% CI 0.03–0.29) using the revised AECG criteria 12. The third study, a cross-sectional population based survey in Turkey by Kabasakal et al, estimated the prevalence of pSS in women aged 18–75 years at 1.56 (95% CI 0.92–2.66) using the European Criteria and 0.72 (95% CI 0.33–1.57) using the revised criteria 13…”
Section: Classification Criteriamentioning
confidence: 99%
“…Three studies [22,24,25] provided an intra-study comparison of the prevalence of the disease when assessed, in the same population, by using both the Preliminary European Criteria and the AECG-criteria. All these three studies confirmed that the prevalence of pSS was lower than previously reported when assessed by the AECG-criteria.…”
Section: Preliminary European Classification Criteria and Aecgcriterimentioning
confidence: 99%
“…The different criteria are not equivalent and may profoundly affect the results of epidemiological studies. For example, in a study from Turkey on adult women, the prevalence of pSS fell from 0.49% using the preliminary European criteria4 to 0.30% according to the AECG criteria 5. New classification criteria were proposed in 2012 and endorsed by the American College of Rheumatology,6 but they are not consensual,7–10 and no epidemiological study has been published to date using these criteria.…”
mentioning
confidence: 99%